Submit a question to our community and get an answer from real people.
Submit

Perfom the indicated operation :f(x)=3x-1 h(x)=x^2-x
(algebra 2)

A.h(f(2))=
B.f(h(2))=
C.f(-5)-h(2))=
D.h(-3)+f(0)=
E.3f(x)+2h(x)=
F.-h(x)-2f(x)=
G.h(x)*f(x)=

Report as

just plug it into whatever its on. f(2) just plug 2 into f(x) and if its fog(x) just plug your answer from g(x) into f(x) and for 3f(x) just multiply

Helpful (2) Fun Thanks for voting Comments (0)
Report as
Add a comment...

I have no idea how to do that jeese....Algebra these days im not in high school yet next year i will be and i dont wanna do that

Helpful Fun Thanks for voting Comments (0)
Report as
Add a comment...

A lot= Huh?

Helpful Fun Thanks for voting Comments (0)
Report as
Add a comment...

I have no clue what I am looking at o.e

Helpful Fun Thanks for voting Comments (0)
Report as
Add a comment...

Answer is E

Helpful Fun Thanks for voting Comments (0)
Report as
Add a comment...

f(x) = 3x - 1, h(x) = x^2 - x
1). h(f(2)) =
f(2) = 3(2)-1 = 5, h(5) = 5^2-5 =
20. ANSWER
2). f(h(2)) =
h(2) = 2^2-2 = 2, f(2) = 3(2)-1 =
5 ANSWER
3). f(-5)-h(2) = 3(-5)-1-(2^2-2) =
-18 ANSWER
4). h(-3) + f(0) = (-3)^2+-3 + 3(0)-1=
5 ANSWER
I'll finish these later. Look under Comments.

Helpful Fun Thanks for voting Comments (3)
Report as
f(x) = 3x-1, h(x) = x^2-x
5). 3f(x)+2h(x) =
3(3x-1) + 2(x^2-x) = 9x-3 + 2x^2 -2x=
2x^2 + 7x - 3. ANSWER
6). -h(x)-2f(x) = -x^2+x-6x+2 =
-x^2 -5x + 2. ANSWER
7). h(x)*f(x) = (x^2-x)(3x-1) =
3x^3 - x^2 - 3x^2 + x =
3x^3 - 4x^2 + x. ANSWER
Report as
you need a medal
Report as
Thank you very much!!!
Report as
Add a comment...
Do you have an answer?
Answer this question...
Did you mean?
Login or Join the Community to answer